The Effect of Chocolate Consumption on The Level of Anxiety in Primigravida Third Trimester Pregnant Women At Jatikalen Health Center Nganjuk District - Meirna Eka Fitriasnani; Anis Nikmatul Nikmah (Universitas STRADA Indonesia, 2020)
Pregnancy is a natural and physiological process but can be a source of stressor anxiety. At the time before delivery, pregnant women often experience stress, fear, and anxiety. Various non-pharmacological efforts were made to reduce the anxiety of pregnant women in facing childbirth. One of them is by consuming chocolate because chocolate contains Phenylethylamine compounds which can increase serotonin in the brain which provides a comfortable and relaxing effect. The purpose of this study was to determine the effect of chocolate consumption on anxiety levels in third-trimester primigravida pregnant women. This research is a pre-experimental study with one group pre-test post-test design. The population was pregnant women aged ≥ 32 weeks primigravida, the sampling technique used was a total population of 16 respondents. The data collected were analyzed using the Wilcoxon test.